Motivation to Study in the Perspective of Islamic Education Psychology - Firdaus Firdaus; Isma Isma; Nursiah Nursiah; Amalia Syurgawi (Journal of Indonesian Progressive Education, 2026)
Education is the primary source of motivation for students to meet their learning objectives, and learning motivation is one of the key elements that significantly influences student achievement. Islamic educational psychology views learning motivation as spiritual values, awareness of worship, and human responsibility in pursuing knowledge in addition to psychological motivation that originates both from within and outside the student. The purpose of this study is to examine the fundamental ideas of learning motivation, the psychological elements that influence learning motivation, and methods for boosting learning motivation in Islamic educational settings. Through the examination of several educational psychology publications and pertinent Islamic sources, a literature study with an analytical descriptive approach is the research methodology employed. The study's findings demonstrate how psychological elements including interests, needs, self-assurance, learning objectives, social surroundings, and teacher support affect students' motivation to learn. According to the Islamic viewpoint, learning motivation is reinforced by the idea that knowledge is paramount, sincere intents, human responsibility awareness, and the goal of receiving benefits and glory in Allah's eyes. Meaningful learning, setting an example for teachers, awarding students, fostering a religious learning atmosphere, and bolstering students' spiritual beliefs are all effective ways to increase learning motivation in Islamic educational institutions.